The Number of Idempotents in Commutative Group Rings of Prime Characteristic - Danchev, P. V. (Sarajevo Journal of Mathematics, 2024)
Suppose $R$ is a commutative unitary ring of prime characteristic $p$ and $G$ is a multiplicative abelian group. The cardinality of the set id$(RG)$ consisting of all idempotent elements in the group ring $RG$, is explicitly calculated only in terms associated with $R$ and $G$ or their sections. 2010 Mathematics Subject Classification. 16S34, 16U60, 20K20, 20K21